Pengaruh Persepsi Harga, Persepsi Risiko, Online Customer Review, dan Sikap terhadap Minat Beli pada Instagram Yuna and Co - Hafsha Rafa Salima; Herwin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims to show the influence of Perceived Price, Perceived Risk, Online Customer Review, and Attitude on Yuna and Co’s instagram Purchase Intention . There are five variables in this research including Perceived Price, Perceived Risk, Online Customer Review, Attitude and Purchase Intention. The researchist used quantitative methods and the sample used in this research amounted 305 respondents who following Yuna and Co’s instagram. The technique used in this research is purposive sampling which is part of non-probability sampling. The research data is analyzed with SPSS 25 shows that Perceived Price Variable have an influence on Purchase Intention, Perceived Risk does not have an influence on Purchase Intention, Online Customer Review have an influence on Purchase Intention, and Attitude have an influence on Purchase Intention .